The influence of laparoscopic adjustable gastric banding and laparoscopic sleeve gastrectomy on weight loss, plasma ghrelin, insulin, glucose and lipids - Hady Razak Hady; Pawel Golaszewski; Robert Lukasz Zbucki; Jacek Dadan (Folia Histochemica et Cytobiologica, 2012)
The aim of this study was to assess the impact of laparoscopic gastric banding and laparoscopic sleeve gastrectomy on the concentration of ghrelin, insulin, glucose, triglycerides, total and HDL-cholesterol, as well as AST and ALT levels in plasma in patients with obesity. The research includes 200 patients operated using LAGB (34 men average age 37.0 ± 12.6 years and 66 women average age 39.18 ± 12.17 years) and LSG (48 men average age 47.93 ± 9.24 years and 52 women, 19 ± 9.33 years). The percentage of effective weight loss, effective BMI loss, concentration of ghrelin, insulin, glucose, triglycerides, total cholesterol, HDL-cholesterol, LDL-cholesterol, ALT, AST and HOMA IR values was taken preoperatively and at 7th day, 1 month, 3 and 6 months after surgery. Both after LSG and after LAGB, statistically significant reduction in BMI, serum insulin, glucose and HOMA IR was noticed in comparison to the preoperative values. Post LAGB, patients showed an increase of ghrelin, while LSG proved ghrelin decreased. Correlations between glucose and BMI loss, and between insulin and BMI loss in both cases are more favorable in the LSG group. Lipid parameters, AST and ALT have undergone declines or  increases in the particular time points. Both techniques cause weight loss and this way lead to changes in the concentration of ghrelin, as well as to the improvement of insulin, glucose, cholesterol and triglycerides metabolism. They reduce metabolic syndrome and multiple comorbidities of obesity.